Comparison between the Acute Pulmonary Vascular Effects of Oxygen with Nitric Oxide and Sildenafil - Day, Ronald W. (Frontiers in Pediatrics, 2015)
Objective. Right heart catheterization is performed in patients with pulmonary arterial hypertension to determine the severity of disease and their pulmonary vascular reactivity. The acute pulmonary vascular effect of inhaled nitric oxide is frequently used to identify patients who will respond favorably to vasodilator therapy. This study sought to determine whether the acute pulmonary vascular effects of oxygen with nitric oxide and intravenous sildenafil are similar. Methods. A retrospective, descriptive study of 13 individuals with pulmonary hypertension who underwent heart catheterization and acute vasodilator testing was performed. The hemodynamic measurements during five phases (21% to 53% oxygen, 100% oxygen, 100% oxygen with 20 ppm nitric oxide, 21% to 51% oxygen, and 21% to 51% oxygen with 0.05 mg/kg to 0.29 mg/kg intravenous sildenafil) of the procedures were compared. Results. Mean pulmonary arterial pressure and pulmonary vascular resistance acutely decreased with 100% oxygen with nitric oxide, and 21% to 51% oxygen with sildenafil. Mean pulmonary arterial pressure (mm Hg, mean ± standard error of the mean) was 38 ± 4 during 21% to 53% oxygen, 32 ± 3 during 100% oxygen, 29 ± 2 during 100% oxygen with nitric oxide, 37 ± 3 during 21% to 51% oxygen, and 32 ± 2 during 21% to 51% oxygen with sildenafil. There was not a significant correlation between the percent change in pulmonary vascular resistance from baseline with oxygen and nitric oxide, and from baseline with sildenafil (r2 = 0.011, p = 0.738). Conclusions. Oxygen with nitric oxide and sildenafil decreased pulmonary vascular resistance. However, the pulmonary vascular effects of oxygen and nitric oxide cannot be used to predict the acute response to sildenafil. Additional studies are needed to determine whether the acute response to sildenafil can be used to predict the long-term response to treatment with an oral phosphodiesterase V inhibitor.